Elastic architected materials with extreme damping capacity. (November 2017) - Haghpanah, Babak; Shirazi, Ahmad; Salari-Sharif, Ladan; Guell Izard, Anna; Valdevit, Lorenzo
Abstract: We report on a new class of elastic architected materials with hybrid unit cells, consisting of discrete elastic elements with non-convex strain energy and one convex (but possibly nonlinear) elastic element, to obtain a reversible multifunctional material with extreme energy dissipation. The proposed design exploits numerically optimized nonlinearities in the force–displacement response of the sub-unit-cell elements to approach the theoretical limit of specific damping capacity in any material, ψ t h = 8 . Specific damping capacities up to ψ = 6 . 02 were experimentally demonstrated, which are far greater than any experimental value previously reported, including in high damping elastomers ( ψ < 4 . 5 ). Remarkably, this damping performance is achieved even with a single unit cell, thus avoiding the need for thick multi-cell designs. Furthermore, the proposed design offers relatively high stiffness and low transmitted stress upon compression. The proposed concept could enable the design of reversible impact-resistant structures with superior crashworthiness and energy dissipation.